SHIGELLEMIA IN A CHILD WITH GASTROENTERITIS: A CASE REPORT AND REVIEW OF MICROBIOLOGY AND MANAGEMENT - Khan, Ejaz Ahmed; Ullah, Inayat; Khan, Ejaz Ahmed (Infectious Diseases Journal of Pakistan, 2023)
Shigellemia is a rare entity of sepsis encountered in individuals having gastroenteritis caused by shigella spp. It is reported to be common in infants, immunocompromised, those having chronic illnesses and post-transplant patients on immunosuppressants. We present a case of a two and half year-old child who developed sepsis like illness during recovery from gastroenteritis. Shigella spp was isolated from blood culture and he responded well to oral antibiotics. This case illustrates the importance of blood and stool cultures that need to be sent in every febrile gastroenteritis case irrespective of immune status. Early detection and prompt treatment will likely improve outcome. Keywords: Shigellemia, Gastroenteritis, Child